Lower Cretaceous ammonites from the Neuquén Basin, Argentina: The Hauterivian genus Spitidiscus - Rawson, Peter F. (2012)
Spitidiscus is a widely-distributed Hauterivian genus that briefly invaded the Neuquén Basin, Argentina, in mid Hauterivian times, well after it first evolved in the west Tethyan area. Its appearance in Argentina is linked with a globally-significant mid Hauterivian sea-level rise. This is marked in the basin by a sharp facies change in the Agrio Formation, from non-marine sandstones of the Avilé Member to marine sediments, often laminated black shales, with Spitidiscus at the base of the overlying Agua de la Mula Member. Our extensive field work has shown that Spitidiscus occurs across the whole basin, where it is represented by two species, Spitidiscus riccardii Leanza and Wiedmann and Spitidiscus kilapiae sp. nov. For most of its vertical range Spitidiscus occurs alone, characterising the S. riccardii Zone. But at the top of its range it is joined by the first crioceratitid ammonites, their appearance marking the base of the Crioceratites schlagintweiti Zone.